Pickling Behavior of Duplex Stainless Steel 2205 in Hydrochloric Acid Solution - Huaying Li; Aichun Zhao (Advances in Materials Science and Engineering)
The oxide-scale structure and pickling behavior of oxided 2205 duplex stainless steel in the electrolytes containing hydrochloric acid were investigated. The oxide scales mainly consist of two layers: the outer layer is dense Fe2O3, and the inner granular is FeCr2O4 spinel. During the pickling process, pittings form around the boundaries of FeCr2O4 particles or interfaces of two kinds of oxides, which results in that the electrolyte can directly react with the chromium-depleted layer along the pittings to produce an “undercut” effect so that the pickling efficiency is improved markedly. The pickling mechanism was discussed, and the model was established.